The Quantum Electronic Partitioning as Modernization in the Studies of the Intermolecular Interactions - Oliveira, Boaz Galdino (Orbital: The Electronic Journal of Chemistry, 2022)
Throughout the years, the evolution in the works involving hydrogen bond based on the direct determination of the interaction energy has become limited in order to characterize the electronic nature and interaction strength of the intermolecular system. Through a quantum mechanical formalism, the electronic partitioning has been considered a modernizing methodology in the studies of intermolecular interactions, unveil it at the light of electrostatic, Exchange, dispersion and induction contributions.